Collection development policy for the Child's Place Multiple Intelligence International School Foundation - Vergara, Marvin M.; Punzalan, Ricardo L. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2005)
The Child's Place Multiple Intelligence International School Library has no written collection development policy that guides it in selecting and acquiring materials for the library's collection. This study shall create a written collection development policy that would suitably tailor to the information and curricular needs of Child's Place-Multiple Intelligence International School Library and its patrons. The objectives of the study are the following: 1) to come up with a written collection development policy in line with the mission and vision of the school; and 2) to ascertain the needs of the patrons of the library.
Descriptive and evaluative methods of research were used in this research work. This research design involves careful selection of subjects, the use of research instruments, well-planned strategy of gathering data and systematic presentation, analysis and interpretation of the meaning and significance of what is described. The respondents are teachers, students, therapists and librarian and library staff of the schools. In determining the sample population, it used stratified sampling method.
The study concludes that: 1) without a strong collection development policy, it will never be possible to completely satisfy all of the information needs of any individual or class of clientele in the service community; 2) no working library exists in Child's Place-Multiple Intelligence International School; 3) a working library is indispensable requirement for Child's Place-Multiple Intelligence International School, for it to be able to provide quality education and to produce information literate individuals and lifelong learners, who will in turn become productive citizens of our country; 4) the findings of this study attest to the fact that without limitations in resources, especially monetary or financial resources and support of the top-level management exert a great influence on the ability of the library to meet the demand of their faculty and students; and 5) the Library is not managed by a professional librarian, without her would make the library as an effective information resources.
The study recommends the following: 1) Child's Place-Multiple Intelligence International School must follow the Collection Development Policy formulated by the researcher based on the results of this research work (please see Appendix D) to be able to help the teachers be up to date with trends, developments, techniques, research, and experimentation in general and in specialized educational fields and must meet the personal information needs of the students; 2) Child's Place-Multiple Intelligence International School Library must be provided with adequate and continuing budgetary support as a separate item from the budget allotted to the different expenditures in the institution it belongs; 3) the need to have a database for the Child's Place-Multiple Intelligence International School Library is imperative; 4) Library collections must be indexed, cataloged and classified properly according to a standard classification system; and 5) the researcher strongly recommends that the findings of this study be utilized in the formulation of a resource-sharing scheme among the other related schools.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Collection development (Libraries) -- Policy statements; School libraries -- Collection development -- Philippines -- San Juan